Knowledge Based Systems for Man-made Disasters Management - Kabbashi, Nassereldeen; Mirghani, Mohamed Elwathig Saeed; Ismail, Noor Hafizah (2011)
Malaysia has experienced several man-made disasters due to the some operation of rapid industrialize development and the number of cases of man-made disaster increases every year.These study reviews and analyses man-made disasters which occurred in Malaysia. The objectives of this study were to identify the causes of man-made disasters to develop an Expert System that could be used as disaster management aid to control the disasters. To achieve these objectives, a review of previous studies of disaster management in Malaysia was carried out. Information research accidents, which occurred in Malaysia,were obtained from several sources. It has been found that Malaysia has experienced 28 disasters during the period 1991 to 2010. The disasters have resulted in 1,649 fatalities, 1,934 injuries, and caused severe damage to properties. Seven technological disasters have resulted in 104 fatalities and 201 injuries. Five man-made disasters have been reviewed in detail.This study shows that the factors, which contributed to the manmade disasters in Malaysia, were mainly due to Social, technical,Organizational, Operational, Investigational and Defences errors.Microsoft Visual Basic Express Edition 2005 was used as a medium for the development of Man-made Disaster Expert System (MMDES). The MMDES is versatile, portable, reliable,and applicable to other emergencies applications. This study provides a tool as an aid for the Safety Managers, as well as the DOSH in decision making and to agents, authorized people and researchers.